Neurological manifestations in dogs with acute leukemia - Lyseight, Filipa L. S.; Pittaway, Charles; Dennis, Ruth; Cherubini, Giunio B. (Frontiers in Veterinary Science, 2024)
Canine acute leukaemia is a rare haematopoietic neoplasm. Neurological abnormalities have been repeatedly reported in dogs with acute leukaemia however description of presentation and findings are limited. To describe the clinical findings in dogs with acute leukaemia presenting with neurological signs as their chief complaint. The database of a private referral hospital was searched for cases that presented to the neurological department with neurological deficits and were subsequently diagnosed with acute leukaemia. Six cases were included; all had neurological clinical signs and abnormal neurological examination. All had a focal neuroanatomical localisation on neurological examination (brain n=4; spinal=2). Of the four dogs with a complete MRI study, there was an ill-defined infiltrative pattern in the central nervous system in three dogs with abnormal signal intensity and loss of grey and white matter differentiation in the brain (n=2) and/or spinal cord (n=2). Other MRI findings included abnormal meningeal enhancement (n=3), changes affecting spinal nerves (n=2) and epaxial muscles (n=2), and lymphadenopathy in the field of view. Bone marrow assessment on MRI showed evidence of signal change (n=3), characterised by loss of normal fat opacity and an abnormal degree of contrast enhancement. The four dogs with cerebrospinal fluid analysis had increased protein with non-specific pleocytosis without evidence of malignant cells. Treatment with cytotoxic medication was implemented in two dogs. Dogs diagnosed with acute leukaemia had a focal neuroanatomical localisation, infiltrative CNS pattern and bone marrow remodulation on MRI with an increase in CSF protein with negative cytology analysis.